Preference Preserved Privacy Protection Scheme for Smart Home Network System Based on Information Hiding - Lina Yang; Haiyu Deng; Xiaocui Dang (IEEE Access, 2020)
Smart home is an emerging form of the Internet of things (IoT), which provides a convenient and comfortable living environment for the smart home users. With the explosive growth of smart home information, people pay more attention to the privacy protection of smart home, including the choice of privacy and effective privacy protection scheme. This paper proposes a privacy protection scheme based on information hiding, the scheme guarantees the sensitive data transmitted securely. First, the smart home Real-time sensor data are classified into sensitive data and non-sensitive data through machine learning, the process can be controlled according to the user's preferences. Second, the sensitive data can be transmitted securely by ordinary channels using method of combination encryption with information hiding. Experiment results show that this scheme can help users to express their preferences to the privacy protection, changing the previous practice that users can only accept the privacy settings provided by the supplier. What's more, the scheme combines encryption with information hiding, providing a double guarantee for the sensitive data during they are transmitted on ordinary channels. Comparing to the previous practice of using encryption merely, this scheme greatly improves the security of data transmission and is more suitable for the real environment.